Evidence of Multi-clrug resistant group G streptococci (GGS) in thePediatrics Ward at Tikrit Teaching Hospital - Akbar Anwar, Sheelan; Hamdi Jasim, Noor; Bahjat Issa, Sinan (Tikrit Journal of Pharmaceutical Sciences, 2023)
During period of Ten months, 200 cases of clinically suspected neonatal septicemia in Kirkuk city were included in this study. The aim of the study was to identify the causative agents of neonatal septicemia and their susceptibility to antibiotics. Blood culture was positive in 79 (39.5%) neonates, 50(63.3%) of them were males and 29(36.7%)were females. Out of 79 positive cases, 53(67.1%) had early-onset septicemia and 26(32.9%) had late-onset septicemia. Gram-negative bacteria were encountered ‘in more than 90 % of these neonates. While gram-positive bacteria represented by Staphylococcus aureus were isolated from 5(6.3%) of neonates only. According to antibiotic susceptibility test it was found that the most effective drug was cefotaxime followed by ciprofloxacin and gentamicin. While most of the isolates were resistant to commonly used antibiotics like Amoxicillin, Ampicillin, Tetracyclin, and erythromycin.